The influence of skipping exercise to body composition and cardiorespiratory fitness index in overweight female adolescents - Edtripany, Gebby Dwi; Riyadi, Hadi; Hardinsyah, Hardinsyah (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
ABSTRACTBackground: The overweight prevalence of adolescents in Indonesia from 2013 to 2018 experienced a significant rising as seen in 13-15 years old age group (expressed in percentage of 8.3 % in 2013 to 11.2 % in 2018) also in the 16-18 years old age group (expressed in percentage of 5.7 % in 2013 to 9.5 % in 2018). An increase of physical activity and improvement of food intake become one solid strategy to reduce the obesity prevalence on female adolescents. Skipping exercise method is able to increase the physical activity level on female adolescents and able to promote the improvement of body composition as well as cardiorespiratory fitness on female adolescents. Objective: analyzes the effect of skipping exercise to changes of body composition and cardiorespiratory fitness on overweight female adolescents by intervention method. Method: subjects in this study were 28 female students from Junior High which experiencing overweight status and have age ranging from 15-17 years old and willing to participate in this research. Design of this study was a quasi experimental applied to 14 subjects within 1 skiping group and 14 subjects within 1 control group. The intervention group received skipping exercise with 4-8 minutes time duration, 3 times in a week for 8 weeks. Prior to intervention and after the intervention, subjects underwent a body composition measurement (body weight, body fat percentage, fat mass, and fat free mass) by employing the BIA, and a cardiorespiratory fitness index measurement by employing a modified Harvard Step Test method.  Result: according to statistical test, there are significant differences found on body composition (body weight, body fat percentage, fat mass, and fat free mass) also in the cardiorespiratory fitness index, in before and after intervention to skipping group (p<0.05), while no significant difference found in control group (p>0.05). Skipping exercise method able to influence the reduction of body composition and an increase to cardiorespiratory fitness index (P<0.05: R2).Conclution: Skipping exercise program has a significant effect on the body composition and on the cardiorespiratory fitness index. The skipping exercise is effective for improving body composition and cardiorespiratory fitness index.  KEYWORDS: Overweight; body composition; cardiorespiratory fitness; Skipping